Adaptive Robust Control based on Backstepping Sliding Mode techniques for Quadrotor UAV under external disturbances - Nettari, Yakoub; Kurt, Serkan; Labbadi, Moussa (ELSEVIER, 2022)
In recent years, the quadrotor has been extensively utilized in military and civic domains because of its high mobility and flexibility in flight. In the presence of parametric uncertainties and external disturbances, it is difficult to control the quadrotor's attitude and position. The goal of this study is to find a solution to this issue. The Euler-Newton formulation is used to describe a full mathematical model of a quadrotor in this article. The attitude and the position's subsystem are the two sections of the quadrotor system. The trajectory tracking control problem of a quadrotor based on the external disturbance is addressed using a backstepping sliding mode control (BSMC) approach. Adaptive strategies are investigated in order to effectively suppress the chattering effect of sliding mode control and to estimate the proposed controller parameters of the position as well as the upper limits of the perturbation of the attitude (ABSMC). Furthermore, the Lyapunov analysis is carried out to ensure the stability of the high nonlinear quadrotor system and the controllers' robustness against variation. Finally, multiple simulations were run on the Matlab/Simulink platform to demonstrate the effectiveness of the proposed controller. This controller's sovereignty is demonstrated by contrasting its performance with other alternatives such as feedback-linearization (FL) and backstepping sliding-mode (BSMC) controllers. Copyright (c) 2022 The Authors. This is an open access article under the CC BY-NC-ND license (https://creativecommons.org/licenses/by-nc-nd/4.0/)
Keywords: Adaptive; Backstepping; Sliding Mode Control; Lyapunov; Newton-Euler; External disturbances; Quadrotor UAV; TRACKING; Automation & Control Systems